Plasma Amino Acid Concentrations in Children With Severe Malaria Are Associated With Mortality and Worse Long-term Kidney and Cognitive Outcomes. (30th September 2022) - Conroy, Andrea L; Tran, Tuan M; Bond, Caitlin; Opoka, Robert O; Datta, Dibyadyuti; Liechty, Edward A; Bangirana, Paul; Namazzi, Ruth; Idro, Richard; Cusick, Sarah; Ssenkusu, John M; John, Chandy C
Abstract: Background: Global changes in amino acid levels have been described in severe malaria (SM), but the relationship between amino acids and long-term outcomes in SM has not been evaluated. Methods: We measured enrollment plasma concentrations of 20 amino acids using high-performance liquid chromatography in 500 Ugandan children aged 18 months to 12 years, including 122 community children and 378 children with SM. The Kidney Disease: Improving Global Outcomes criteria were used to define acute kidney injury (AKI) at enrollment and chronic kidney disease (CKD) at 1-year follow-up. Cognition was assessed over 2 years of follow-up. Results: Compared to laboratory-defined, age-specific reference ranges, there were deficiencies in sulfur-containing amino acids (methionine, cysteine) in both community children and children with SM. Among children with SM, global changes in amino acid concentrations were observed in the context of metabolic complications including acidosis and AKI. Increases in threonine, leucine, and valine were associated with in-hospital mortality, while increases in methionine, tyrosine, lysine, and phenylalanine were associated with postdischarge mortality and CKD. Increases in glycine and asparagine were associated with worse attention in children <5 years of age. Conclusions: Among children with SM, unique amino acid profiles are associated with mortality, CKD, and worse attention. Abstract : Children with severe malaria have widespread changes in amino acid levels at hospital admission associated with metabolic complications at presentation, predicting in-hospital and postdischarge mortality, chronic kidney disease at 1-year follow-up, and worse attention over 2 years of follow-up.